2021
DOI: 10.7759/cureus.17969
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Systemic Lupus Erythematosus: A 2021 Update on Diagnosis, Management, and Current Challenges

Abstract: Patients with systemic lupus erythematosus (SLE) experience neuropsychiatric symptoms. The term neuropsychiatric SLE (NPSLE) is a generic term that refers to a series of neurological and psychiatric symptoms directly related to SLE. In approximately 30% of patients with neuropsychiatric symptoms, SLE is the primary cause (NPSLE), and symptoms manifest more frequently around SLE onset. Neurovascular and psychotic conditions can also lead to NPSLE. Pathogenesis of NPSLE is implicated in both neuroinflammatory an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
98
0
12

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(112 citation statements)
references
References 44 publications
2
98
0
12
Order By: Relevance
“…Diagnosis of NPSLE is the lack of specific and sensitive CSF testing ( 6 ). As previous studies have shown, some autoantibodies have been suggested as a potential biomarker for diagnosis and therapeutic decision, such as antineuronal, anti-ribosomal P, and ant-NR2 antibodies ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Diagnosis of NPSLE is the lack of specific and sensitive CSF testing ( 6 ). As previous studies have shown, some autoantibodies have been suggested as a potential biomarker for diagnosis and therapeutic decision, such as antineuronal, anti-ribosomal P, and ant-NR2 antibodies ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of NPSLE is the lack of specific and sensitive CSF testing ( 6 ). As previous studies have shown, some autoantibodies have been suggested as a potential biomarker for diagnosis and therapeutic decision, such as antineuronal, anti-ribosomal P, and ant-NR2 antibodies ( 6 ). Autoantibodies may be detected in the CSF as a result of the transfer of peripherally produced autoantibodies across a breached blood brain barrier or increased intrathecal production ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Systemic lupus erythematosus (SLE) is an autoimmune inflammatory disease that predominantly affects women between puberty and menopause [ 1 , 2 ]. SLE patients can suffer from clinical manifestations including arthritis, serositis, nephritis, rashes, scars, depigmentation, skin dimpling, hair loss, or neuropsychiatric problems [ 3 ], which have great impacts on quality of life (QoL) in this population [ 4 ]. Sexual problem is an important aspect of QoL and it is of great importance for SLE patients because it occurs predominantly in women with female to male ratio of 9:1 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%